EFFECTIVENESS EVALUATION OF THE CONVERSION COATINGS APPLICATION ON TITANIUM ALLOYS IN CONTACT WITH GFRP UNDER NOMINALLY STATIONARY CONTACT CONDITIONS - Khimko, Andrii; Khimko, Margarita; Makarenko, Ruslan; Tokaruk, Vitalii (Problems of Friction and Wear, 2026)
Titanium products are very often used conversion coatings that are formed on the metal surface as a result of a chemical reaction with reagents or the environment. The purpose of using such coatings is to increase corrosion protection, ensure better adhesion with paint coatings, decorative aspect, and also increase wear-resistant characteristics. The paper analyzes the use of conversion coatings on titanium alloys for wear protection. Tests have shown that conversion coatings increase the wear resistance of titanium alloy Ti5Al5V5Мо1Cr1Fe for anodic coating by 10% and by 6% for phosphate coating in combination with GFRP. The shallow depth of the coating up to 20 μm and insufficient hardness only provide protection from reinforcing glass fibers of the composite material for a while and then only enhance the damage effect. When E-glass fibers come into contact with conversion coatings, deep grooves are formed at the micro level, which are located in the sliding direction. Due to shearing and setting, the products of conversion coatings, titanium oxides and glass fiber particles are mixed on the friction surface into a tribological layer that mainly has an abrasive effect. As a result of fretting processes, microcracks and areas of titanium coating delamination are formed on the surface near the grain boundaries, which increase the destruction of the titanium surface. Anodizing provides greater protection due to the formation of a film that is 40 % harder than phosphating.